Assessment of DNA Susceptibility to Denaturation as a Marker of Chromatin Structure. Issue 1 (16th October 2019) - Darzynkiewicz, Zbigniew; Halicka, Dorota H.; Zhao, Hong; Li, Jiangwei
Abstract: The susceptibility of DNA in situ to denaturation is modulated by its interactions with histone and nonhistone proteins, as well as with other chromatin components related to the maintenance of the 3D nuclear structure. Measurement of DNA proclivity to denature by cytometry provides insight into chromatin structure and thus can be used to recognize cells in different phases of the cell cycle, including mitosis, quiescence (G0 ), and apoptosis, as well as to identify the effects of drugs that modify chromatin structure. Particularly useful is the method's ability to detect chromatin changes in sperm cells related to DNA fragmentation and infertility. This article presents a flow cytometric procedure for assessing DNA denaturation based on application of the metachromatic property of acridine orange (AO) to differentially stain single‐ versus double‐stranded DNA. This approach circumvents limitations of biochemical methods of examining DNA denaturation, in particular the fact that the latter destroy higher orders of chromatin structure and that, being applied to bulk cell populations, they cannot detect heterogeneity of individual cells. Because the metachromatic properties of AO have also found application in other cytometric procedures, such as differential staining of RNA versus DNA and assessment of lysosomal proton pump including autophagy, to avert confusion between these approaches and the use of this dye in the DNA denaturation assay, these AO applications are briefly outlined in this unit as well. © 2019 by John Wiley & Sons, Inc. Basic Protocol : Differential staining of single‐ versus double‐stranded DNA with acridine orange